Efecto de cuatro dosis de trihormona en el cultivo de tomate (Lycopersicumesculentum) hibrido wsx 2205 f-1, bajo condiciones agroecológicas en la provincia de Lamas - Rengifo Portocarrero, Rafael (2013)
In vegetables, tomato fruits have a wide acceptance and preference for its taste qualities and the possibility of its wide use in fresh or processed state in multiple ways, and thus constitutes one of the main vegetables grown in the world. Currently there is a pervasive tendency to constantly seek alternative production systems used in the field of agriculture with the laudable aim of raising crop yields and cause an increase in the availability of food for the growing population of mankind. Trihormonas Agrostemin The GL is a new liquid formulation with organic protohormonas glycosilicadas. It is a natural extract from fresh seaweed Ascophillum nodosum containing no artificial additives (100% natural), which promote plant within the natural release of auxins, cytokinins and giberalina in a balanced way. As the world population continues to grow, fertile land and water quality continue to decline and the migration of people to the cities. In this work, the performance is studied, the effect of hormones and driving the tomato crop under the agroecological system, using organic and foliar fertilizers, which is intended to provide the appropriate techniques to good handling and driving culture tomato under this system, also help people produce their healthy vegetables every day.